Glyphosate herbicide toxicity effects on red hybrid tilapia (Oreochromis sp.) - Muhammad, Umar Abubakar (2019)
Glyphosate [N-(phosphonomethyl) glycine] is among the most broadly and generally recognised broad-spectrum herbicides used in agriculture due to its low cost and effectiveness in weed management. The pollution of glyphosate in the aquatic environment can be via water run-off from agricultural lands, or by spray drift, aerial spraying or due to industrial discharge, which may be seen as a threat to aquatic biota. Fish is one of the best organisms to study the toxicological aspects of glyphosate. To date, very few studies have been done with high purity glyphosate due to the cost factor, of which this study aims to accomplished. Fish was procured and acclimatized to the laboratory condition within ten days before the commencement of the experiment. A 4 days bioassay was carried out using red hybrid tilapia (Oreochromis sp.) as the test organisms to ascertain lethal concentration (LC50) of glyphosate using arithmetic and probit methods. After determining the LC50, fish were exposed to different concentrations (0, 25, 50, 100 and 150 mg/L) of glyphosate herbicide for 4- and 49-days to evaluate its toxicity through changes in fish behaviour, hematological, biochemical, histopathological as well as changes in the growth pattern of the fish. The major physicochemical parameters of the water were ascertained. The water quality parameters during the experiments ranged are temperature (25-29℃), dissolved oxygen (5.3-9.3 mg/L) and pH (6.5-7.4) respectively. The LC50 values of glyphosate were 250 mg/L (arithmetic) and 215 mg/L with 162 and 282 mg/L as lower and upper 95% confidence limit (Probit). Fish mortality rate positively correlated with the increase in glyphosate concentration. Glyphosate exerts fewer effects on the behaviour of red hybrid tilapia at low concentrations, but at higher concentrations of 50 mg/L and above various behavioural changes including air gasping, erratic swimming, fin movement, mucus secretions, hemorrhages, and loss of scale were evident. There was significant concentration-dependent decrease between the control and exposed fish in all haematological parameters examined. The total serum protein showed a significant decrease between the control and exposed fish. There was an increase in the values of total bilirubin, alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, and gamma-glutamyl transferase in both 4- and 49-days exposure periods. A significant decline was recorded in the cholinesterase enzyme activities in all organs and substrate except the spleen, kidney and gills using PTC substrate during 4 days exposure and gills using BTC substrate during the 49 days glyphosate exposure. BTC and ATC substrates recorded higher activities in the liver and brain both during 4- and 49-days exposure periods. Glyphosate herbicide significantly declined the protein content in all organs during 4- and 49-days toxicity testing with the exception of ovary which shows no significant changes during both toxicity testing. The overall growth performance of the fish was hindered due to exposure to glyphosate herbicide with a reduction in the length (26.3±2.4 to 23.3±1.6 cm), weight (198±5.9 to 175±2.79 g), food conversion ratio (0.21 to 0.02), specific growth rate (4.6 to 4.57), and condition factor (1.28 to 0.95) between the control and glyphosate treated fish. A significant decrease was observed in the hepato-somatic and gonadal-somatic indices of the fish exposed to glyphosate. Glyphosate exposure also resulted in different histopathological changes, with fewer changes in the ovary of red hybrid tilapia. In the liver, hepatopancreas degeneration and its partial detachment from the liver parenchyma, congested blood capillaries, necrosis, hemosiderin deposit, reduced number of mitochondria, pyknosis, degeneration of nucleolus, cytoplasmic vacuolation, and damaged mitochondria result histopathological changes recorded as a result of glyphosate exposure to red hybrid tilapia. Hemosiderin deposit, mitochondria vacuolation, the rapture of the nuclear membrane, margination of chromatin as well as melanin deposit were seen in the spleen of fish. Lifting and congestion of primary and secondary gill lamellae, oedema of interdigitate area, hyperplasia, hypertrophy, mitochondrial degeneration, karyolysis, cellular membrane degeneration were observed in the gills of the fish after glyphosate exposure. Widening of the Bowman’s corpuscular space, infiltration of inflammatory cells, tubular degeneration and necrosis, hemosiderin deposit, karyolysis, mitochondria degeneration and vacuolation and dissolution of the cellular membrane were the resulted histopathological alterations seen in the kidney of the fish exposed to glyphosate herbicide. In the brain, partial detachment of the neuronal cells, necrosis of neuronal and glial cells, congestion and dilation of blood vessels, vacuolation of neurophil and glial cells axonal and mitochondrial degeneration and cytoplasmic oedema were the changes observed. Reduced number of previtellogenic follicles and mature yolk granules, increased empty spaces within the mature follicles and degeneration and vacuolation of mitochondria were observed in the ovary of the fish exposed to glyphosate herbicide. According to the findings of this research, exposure of red hybrid tilapia to glyphosate herbicide resulted into overall decline in the health status of the fish. These findings may indicate a health risk for red hybrid tilapia and other aquatic animals exposed to glyphosate in aquatic ecosystems.